1992
DOI: 10.1128/aac.36.1.172
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind randomized study of the effect of infusion rates on toxicity of amphotericin B

Abstract: Results of a double-blind randomized non-crossover study of rapid (45 min) versus slow (4 h) infusion of amphotericin B administered to 20 patients with proven or suspected fungal infection are reported. Toxicity was higher in the rapid infusion group than it was in the slow infusion group (mean total 7-day chill score, 173 ± 276 versus 20 ± 30 [P < 0.01]; mean total 7-day dosage of meperidine required to abate rigors, 180 ± 133 versus 58 ± 78 mg [P < 0.05]; and mean maximum total 7-day pulse rise, 225 ± 64 ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 5 publications
0
21
0
2
Order By: Relevance
“…There is some evidence that a relatively slow infusion of AmB (4 h v. 45 min) reduces the occurrence of infusion-related adverse effects (Ellis et al, 1992). Although the administration of AmB by continuous infusion over 24 h appears to reduce nephrotoxicity (Eriksson et al, 2001), such long infusions were not feasible at Amudat Hospital.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that a relatively slow infusion of AmB (4 h v. 45 min) reduces the occurrence of infusion-related adverse effects (Ellis et al, 1992). Although the administration of AmB by continuous infusion over 24 h appears to reduce nephrotoxicity (Eriksson et al, 2001), such long infusions were not feasible at Amudat Hospital.…”
Section: Discussionmentioning
confidence: 99%
“…But importantly, we administer D‐AmB as a 24‐hour continuous infusion (24 h‐D‐AmB) to allow better tolerability and longer treatment duration . Slow infusion rates are known to lead to fewer side effects and less toxicity than 4‐hour infusions . We here report the safety and efficacy of D‐AmB given as a 24‐hour continuous infusion in patients with acute myeloid leukaemia (AML) and severe prolonged neutropenia following myeloablative chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…[23], [24] A meta-analysis on the adverse events of the antifungal agents used against IFIs has shown that AmB deoxycholate is the most nephrotoxic AmB formulation, while the lipid formulations are less nephrotoxic. [25] Several lines of evidence from pharmacokinetic and non-comparative clinical studies have suggested that continuous infusion of AmB deoxycholate might reduce the nephrotoxicity of the drug [26], [27], [28].…”
Section: Discussionmentioning
confidence: 99%